Probing Into E-commerce Logistics: A Strategic Growth Option of Serbada Company - Andrian Indramawan; Jacob Donald Tan; John Tampil Purba (Jurnal Ilmu Manajemen & Ekonomika, 2018)
E-commerce marketplace is prominent in today ‘s society era of buying and selling products without having to leave the doorsteps. One important stakeholder group involved in the process of e-commerce is logistics. Logistic companies facilitate the delivery from one destination to another with punctuality and security of the products keys in establishing trust between the buyer, seller, and the e-commerce hubs. Hence by means of participant observation, this case study research investigates the key success factors of how an e-commerce firm manages its collaborations with logistic partners, as well as how the firm utilizes its strengths and opportunities take advantage of the market while minimizing its weaknesses and threats. The researchers used Business Model Canvas and TOWS in their analytical process